Trust in health care and vaccine hesitancy - Elisabetta Lalumera (Rivista di Estetica, 2019)
Health care systems can positively influence our personal decision-making and health-related behavior only if we trust them. I propose a conceptual analysis of the trust relation between the public and a healthcare system, drawing from healthcare studies and philosophical proposals. In my account, the trust relation is based on an epistemic component, epistemic authority, and on a value component, the benevolence of the healthcare system. I argue that it is also modified by the vulnerability of the public on healthcare matters, and by the system’s credibility. I apply my proposed analysis of public trust in health care systems to the phenomenon of vaccine hesitancy, a tendency to question vaccine policies, and to seek alternative vaccine schedules or to refuse vaccination. Understanding the role of trust and its components can be key to understanding the phenomenon.